Temperature-controlled targeted release composite inhibitor as well as preparation method and application thereof
By preparing a composite resistor with a temperature-controlled targeted release, using the combination of water-absorbing gel and antioxidant, the problem that the composite resistor in the prior art cannot effectively cover the entire process of coal oxidation reaction is achieved, and more efficient Blocking effect and utilization rate.
Patent Information
- Application Number
- CN202411658151.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-02-07
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing composite inhibitors cannot effectively cover the entire process of coal oxidation reaction, resulting in poor resistance and low utilization.
Using a temperature-controlled targeted release composite resistor, which consists of a water-absorbing gel (physical resistor) and an antioxidant (chemical resistor), is prepared through neutralization reaction, polymerization reaction and adsorption steps to ensure that the antioxidant is Release slowly at different temperatures.
It improves the resistance effect and utilization rate, improves the stability of antioxidants, ensures the entire process of coal oxidation reaction, and reduces the risk of coal spontaneous combustion.
Smart Images

Figure CN119390898A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of inhibitors, and in particular to a temperature-controlled targeted-release composite inhibitor and a preparation method and application thereof. Background Art
[0002] In order to prevent coal from spontaneous combustion, inhibitors are added during the storage and transportation of coal to inhibit the oxidation reaction of coal. At present, commonly used inhibitors are divided into physical inhibitors, chemical inhibitors and composite inhibitors. Among them, physical inhibitors mainly based on salts, halides and foams mainly act on the first stage of coal oxidation reaction; chemical inhibitors mainly based on antioxidants mainly act on the second and third stages. Each type of inhibitor has its own advantages and disadvantages and action mechanism. The use of physical inhibitors or chemical inhibitors alone cannot completely cover the entire process of coal oxidation reaction. Composite inhibitors are compounded by physical inhibitors and chemical inhibitors, but because composite inhibitors make physical inhibitors and chemical inhibitors contact with coal at the same time, it cannot guarantee that chemical inhibitors can act on the oxidation reaction process of coal in a timely and effective manner. At the same time, it will also reduce the utilization rate of chemical inhibitors and increase costs.
[0003] Therefore, it is urgent to develop a composite inhibitor with temperature-controlled targeted release, so that the components in the composite inhibitor can act on the different stages of the coal oxidation reaction in a timely and effective manner, covering the entire process of the coal oxidation reaction, and improving the inhibition effect and its utilization rate. Summary of the invention
[0004] The purpose of the present invention is to provide a temperature-controlled targeted release composite inhibitor and a preparation method and application thereof in view of the deficiencies in the prior art.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] The present invention provides a method for preparing a temperature-controlled targeted release composite inhibitor, comprising the following steps:
[0007] (1) neutralizing an acrylic acid solution, cellulose, acrylamide and water to obtain an intermediate solution;
[0008] (2) subjecting the initiator, the crosslinking agent and the intermediate solution to a polymerization reaction to obtain a water-absorbing gel;
[0009] (3) The water-absorbing gel is immersed in an aqueous solution of an antioxidant for adsorption, thereby obtaining a temperature-controlled targeted release composite inhibitor.
[0010] Preferably, the cellulose comprises one or more of methyl cellulose, hydroxymethyl cellulose, hydroxypropyl methyl cellulose and sodium carboxymethyl cellulose;
[0011] The initiator comprises potassium persulfate, an azo compound or 2-hydroxy-2-methyl-1-phenylpropanone;
[0012] The cross-linking agent was N,N'-methylenebisacrylamide;
[0013] The antioxidant comprises one or more of ascorbic acid, tea polyphenols, anthocyanidins and grape seed extract.
[0014] Preferably, the acrylic acid solution in step (1) is a mixture of acrylic acid and sodium hydroxide, the neutralization degree of the acrylic acid solution is 40-90%, the mass ratio of cellulose to acrylic acid is 5-30:100, the mass ratio of acrylamide to acrylic acid is 18-45:100, and the mass volume ratio of cellulose to water is 5-30g:200mL.
[0015] Preferably, the temperature of the neutralization reaction in step (1) is 60 to 80° C., and the time of the neutralization reaction is 20 to 40 minutes.
[0016] Preferably, the mass ratio of the initiator in step (2) to the acrylic acid in the acrylic acid solution in step (1) is 0.2-1:100, and the mass ratio of the crosslinking agent to the acrylic acid in the acrylic acid solution in step (1) is 0.07-0.2:100.
[0017] Preferably, the polymerization reaction temperature in step (2) is 60-80° C., and the polymerization reaction time is 1-3 hours; and the polymerization reaction is carried out in an oxygen-free environment.
[0018] Preferably, in step (3), the mass ratio of the water-absorbing gel to the antioxidant is 0.8-1.2:1, and the mass volume ratio of the antioxidant to water in the antioxidant aqueous solution is 1 g: 80-200 mL.
[0019] Preferably, the adsorption time in step (3) is 90 to 150 minutes.
[0020] The present invention also provides a temperature-controlled targeted-release composite inhibitor prepared by the preparation method, wherein the particle size of the temperature-controlled targeted-release composite inhibitor is 80-160 meshes.
[0021] The present invention also provides the use of the temperature-controlled targeted release composite inhibitor in inhibiting coal spontaneous combustion, which can be achieved by mixing the temperature-controlled targeted release composite inhibitor with coal, wherein the mass ratio of the temperature-controlled targeted release composite inhibitor to coal is 1:3-8.
[0022] The beneficial effects of the present invention include the following:
[0023] 1) The temperature-controlled targeted-release composite inhibitor of the present invention is composed of a water-absorbing gel (physical inhibitor) and an antioxidant (chemical inhibitor). The water-absorbing gel presents a three-dimensional network structure, and the cellulose therein contains a large number of water-absorbing groups, which can wrap the solution containing the antioxidant in the three-dimensional network structure, thereby effectively improving the stability of the antioxidant, improving the problem of weakened coal spontaneous combustion inhibition effect due to the decomposition of the antioxidant during storage and transportation, and improving the inhibitory effect.
[0024] 2) The water-absorbing gel can play a role in physical cooling and fire extinguishing, and is a biodegradable material; as the temperature rises, the water-absorbing gel slowly releases antioxidants, which continuously inhibit the spontaneous combustion of coal, solving the problem of poor inhibitory effect of single physical inhibitors or chemical inhibitors in the prior art. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 The composite inhibitor for temperature-controlled targeted release of Example 1 was respectively dissolved in KCl aqueous solution, NaCl aqueous solution and MgCl aqueous solution at different mass concentrations. 2 Absorption rate in aqueous solution;
[0026] Figure 2 The composite inhibitor for temperature-controlled targeted release of Example 1 at different temperatures was respectively dissolved in water, MgCl with a mass concentration of 0.2%, 2 Absorption rate in aqueous solution;
[0027] Figure 3 is the repetitive liquid absorption ratio of the temperature-controlled targeted release composite inhibitor in Example 1 in water;
[0028] Figure 4 The CO content changes during the raw coal oxidation process of Application Example 1 and Comparative Examples 1 to 3 are shown;
[0029] Figure 5 The inhibition rates of application example 1 and comparative examples 1 to 3 during the raw coal oxidation process;
[0030] Figure 6 This is the inhibition mechanism of the temperature-controlled targeted-release composite inhibitor of the present invention. DETAILED DESCRIPTION
[0031] The present invention provides a method for preparing a temperature-controlled targeted release composite inhibitor, comprising the following steps:
[0032] (1) neutralizing an acrylic acid solution, cellulose, acrylamide and water to obtain an intermediate solution;
[0033] (2) subjecting the initiator, the crosslinking agent and the intermediate solution to a polymerization reaction to obtain a water-absorbing gel;
[0034] (3) The water-absorbing gel is immersed in an aqueous solution of an antioxidant for adsorption, thereby obtaining a temperature-controlled targeted release composite inhibitor.
[0035] In the present invention, the cellulose preferably comprises one or more of methyl cellulose, hydroxymethyl cellulose, hydroxypropyl methyl cellulose and sodium carboxymethyl cellulose;
[0036] The initiator preferably comprises potassium persulfate, an azo compound or 2-hydroxy-2-methyl-1-phenylpropanone;
[0037] The cross-linking agent is preferably N,N'-methylenebisacrylamide;
[0038] The antioxidant preferably comprises one or more of ascorbic acid, tea polyphenols, anthocyanidins and grape seed extract.
[0039] In the present invention, cellulose has good water solubility and biocompatibility, and has thickening and stabilizing effects. Hydroxypropyl methylcellulose contains a large amount of -OH in its molecular structure, which can form hydrogen bonds with water molecules after being dissolved in water, and bind water molecules in a three-dimensional network structure to form a solution with a certain viscosity, thereby enhancing the stability of the water-absorbing gel. The cross-linking agent can change the cross-linking density of the material, which is an important factor affecting the swelling and water absorption of the water-absorbing gel. By adding an appropriate amount of cross-linking agent, more network nodes are formed on the long-chain macromolecules, and the chains can be cross-linked to form a three-dimensional network structure, thereby increasing the cross-linking density.
[0040] In the present invention, the acrylic acid solution in step (1) is preferably a mixed solution of acrylic acid and sodium hydroxide, and the neutralization degree of the acrylic acid solution is preferably 40-90%, more preferably 50-80%, and more preferably 60-70%; the mass ratio of cellulose to acrylic acid is preferably 5-30:100, more preferably 10-25:100, and more preferably 15-22.5:100; the mass ratio of acrylamide to acrylic acid is preferably 18-45:100, more preferably 25-40:100, and more preferably 30-33.75:100; the mass volume ratio of cellulose to water is preferably 5-30 g:200 mL, more preferably 6-25 g:200 mL, and more preferably 10-20 g:200 mL.
[0041] In the present invention, after acrylic acid is neutralized by sodium hydroxide, negatively charged groups are grafted onto the long chains of the polymer, forming electrostatic repulsion, which makes the three-dimensional network structure have a tendency to expand. However, if the neutralization is too high, more sodium ions will react with the hydrophilic groups to copolymerize, thereby shielding or reducing the electrostatic repulsion, making the three-dimensional network structure smaller and reducing the expansion performance of the water-absorbing gel.
[0042] In the present invention, in step (1), cellulose and water are preferably first mixed to obtain a cellulose aqueous solution, the cellulose aqueous solution is heated to a temperature required for a neutralization reaction, and then an acrylic acid solution and acrylamide are sequentially added to perform a neutralization reaction. The cellulose and water are preferably stirred during the mixing process, and the stirring speed is preferably 20 to 40 rpm, more preferably 30 rpm, and the stirring is stopped after the cellulose is completely dissolved.
[0043] In the present invention, stirring is preferably performed during the neutralization reaction in step (1), and the stirring speed is preferably 20 to 40 rpm, and more preferably 30 rpm.
[0044] In the present invention, the temperature of the neutralization reaction in step (1) is preferably 60 to 80°C, more preferably 65 to 75°C, and more preferably 70°C; the time of the neutralization reaction is preferably 20 to 40 min, more preferably 25 to 35 min, and more preferably 30 min.
[0045] In the present invention, the mass ratio of the initiator in step (2) to the acrylic acid in the acrylic acid solution in step (1) is preferably 0.2 to 1:100, more preferably 0.4 to 0.75:100, and more preferably 0.6:100; the mass ratio of the crosslinking agent to the acrylic acid in the acrylic acid solution in step (1) is preferably 0.07 to 0.2:100, more preferably 0.1 to 0.18:100, and more preferably 0.15:100.
[0046] In the present invention, the amount of initiator not only affects the long chain length of the water-absorbing gel, but also affects the morphology and molecular weight of the water-absorbing gel; the initiator can generate more grafting sites on the cellulose molecular chain to increase water absorption. However, if the amount of initiator is too large, there will be too many corresponding reaction sites, which will accelerate the reaction rate and easily cause heat to be difficult to diffuse and cause an implosion reaction.
[0047] In the present invention, in step (2), the initiator is preferably first added to the intermediate solution, and then the cross-linking agent is added.
[0048] In the present invention, the temperature of the polymerization reaction in step (2) is preferably 60-80°C, more preferably 65-75°C, and more preferably 70°C; the time of the polymerization reaction is preferably 1-3h, more preferably 1.5-2.5h, and more preferably 2h; the polymerization reaction is preferably carried out in an anaerobic environment.
[0049] In the present invention, after the polymerization reaction in step (2) is completed, the reaction product is preferably dried and crushed in sequence to obtain a water-absorbing gel; the drying temperature is preferably 50 to 70° C., more preferably 60° C.; the drying time is preferably 4 to 12 hours, more preferably 8 hours; the particle size of the water-absorbing gel is preferably 80 to 100 mesh, more preferably 90 mesh.
[0050] In the present invention, the mass ratio of the water-absorbing gel and the antioxidant in step (3) is preferably 0.8-1.2:1, more preferably 0.9-1.1:1, and more preferably 1:1; the mass volume ratio of the antioxidant to water in the antioxidant aqueous solution is preferably 1g:80-200mL, more preferably 1g:120-160mL, and more preferably 1g:140-150mL.
[0051] In the present invention, the adsorption time in step (3) is preferably 90 to 150 min, more preferably 100 to 140 min, and even more preferably 120 min.
[0052] The present invention also provides a temperature-controlled targeted release composite inhibitor prepared by the preparation method. The particle size of the temperature-controlled targeted release composite inhibitor is preferably 80-160 meshes, more preferably 100-140 meshes, and more preferably 120 meshes.
[0053] The present invention also provides the use of the temperature-controlled targeted-release composite inhibitor in inhibiting coal spontaneous combustion, which can be achieved by mixing the temperature-controlled targeted-release composite inhibitor with coal. The mass ratio of the temperature-controlled targeted-release composite inhibitor to coal is preferably 1:3-8, further preferably 1:4-7, and more preferably 1:5-6.
[0054] In the present invention, the inhibition mechanism of the temperature-controlled targeted release composite inhibitor in inhibiting coal spontaneous combustion is embodied in two aspects: physical inhibition and chemical inhibition:
[0055] Physical inhibition mechanism:
[0056] ① Isolation of coal-oxygen contact: The cellulose in the temperature-controlled targeted release composite inhibitor improves the adhesion of the composite inhibitor. After mixing with coal, the composite inhibitor can quickly and firmly cover the coal surface and penetrate into the coal gaps to prevent air from contacting the coal;
[0057] ② Evaporation heat absorption: The temperature-controlled targeted release composite inhibitor has good water absorption, and the complex three-dimensional network structure helps to lock water inside the composite inhibitor, improve the water retention performance of the composite inhibitor, avoid water evaporation, and improve the utilization rate of water evaporation heat absorption capacity.
[0058] Chemical inhibition mechanism:
[0059] The main components of the chemical inhibition process are antioxidants such as tea polyphenols, which contain a large number of phenolic hydroxyl groups in their molecular structure. The hydrogen atoms on the phenolic hydroxyl groups are easily captured by other free radicals (such as ROO·) to generate semiquinone free radicals. Semiquinone free radicals have low activity and will not cause new chain reactions, but they can combine with other free radicals (such as R·) to generate stable ether bonds; at the same time, they can also undergo etherification reactions with alcohol hydroxyl groups. The above reaction process will consume the free radicals (ROO·, R· and ROH) required for the free radical chain reaction of coal, resulting in the forced interruption of the free radical chain reaction of coal, thereby preventing further oxidation of coal.
[0060] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0061] Example 1
[0062] 3 g of hydroxypropyl methylcellulose and 100 mL of deionized water were mixed, and stirred at 30° C. and 30 rpm until the hydroxypropyl methylcellulose was completely dissolved to obtain a cellulose aqueous solution. The cellulose aqueous solution was heated to 70° C., and then 20 g of an acrylic acid solution (a mixed solution of acrylic acid and sodium hydroxide) with a neutralization degree of 60% and 4.5 g of acrylamide were sequentially added to the cellulose aqueous solution, and stirred at 70° C. and 30 rpm for 30 minutes for neutralization reaction to obtain an intermediate solution.
[0063] NH was introduced into the reaction vessel at a rate of 100 mL / min. 3 To form an anaerobic environment, 0.1 g potassium persulfate was added to the intermediate solution under anaerobic environment, and the mixture was stirred at 30 rpm for 10 min. Then 0.02 g N,N'-methylenebisacrylamide was added, and the polymerization reaction was carried out at 70 °C for 2 h. After the polymerization reaction was completed, the introduction of NH 3 The product of the polymerization reaction was dried at 60°C for 8 hours and crushed to obtain a water-absorbing gel with a particle size of 90 mesh.
[0064] 1g of tea polyphenols was completely dissolved in 120mL of deionized water to obtain a tea polyphenols aqueous solution, 1g of water-absorbing gel was added to the tea polyphenols aqueous solution, and adsorbed for 120min. The adsorbed product was placed at 60°C and dried for 24h to obtain a temperature-controlled targeted release composite inhibitor.
[0065] The particle size of the temperature-controlled targeted-release composite inhibitor prepared in this example is 100 meshes.
[0066] Example 2
[0067] 5 g of hydroxymethyl cellulose and 100 mL of deionized water were mixed, and stirred at 30° C. and 20 rpm until the hydroxymethyl cellulose was completely dissolved to obtain a cellulose aqueous solution. The cellulose aqueous solution was heated to 60° C., and then 22 g of an acrylic acid solution (a mixed solution of acrylic acid and sodium hydroxide) with a neutralization degree of 40% and 3.1 g of acrylamide were sequentially added to the cellulose aqueous solution, and stirred at 60° C. and 20 rpm for 40 minutes for neutralization reaction to obtain an intermediate solution.
[0068] NH was introduced into the reaction vessel at a rate of 100 mL / min. 3 To form an anaerobic environment, 0.068 g of azobisisobutyronitrile was added to the intermediate solution under anaerobic environment, and the mixture was stirred at 30 rpm for 10 min. Then, 0.012 g of N,N'-methylenebisacrylamide was added, and the polymerization reaction was carried out at 80 °C for 1 h. After the polymerization reaction was completed, the introduction of NH 3 The product of the polymerization reaction was dried at 60°C for 12 hours and crushed to obtain a water-absorbing gel with a particle size of 80 meshes.
[0069] 1g of anthocyanin was completely dissolved in 150mL of deionized water to obtain an anthocyanin aqueous solution, 0.8g of water-absorbing gel was added to the anthocyanin aqueous solution, and adsorbed for 150min. The adsorbed product was placed at 60°C and dried for 24h to obtain a temperature-controlled targeted release composite inhibitor.
[0070] The particle size of the temperature-controlled targeted-release composite inhibitor prepared in this example is 120 meshes.
[0071] Example 3
[0072] 12.5 g of sodium carboxymethyl cellulose and 100 mL of deionized water were mixed, and stirred at 30° C. and 40 rpm until the sodium carboxymethyl cellulose was completely dissolved to obtain a cellulose aqueous solution. The cellulose aqueous solution was heated to 80° C., and then 225 g of an acrylic acid solution (a mixed solution of acrylic acid and sodium hydroxide) with a neutralization degree of 80% and 50 g of acrylamide were sequentially added to the cellulose aqueous solution, and stirred at 80° C. and 40 rpm for 20 minutes for neutralization reaction to obtain an intermediate solution.
[0073] NH was introduced into the reaction vessel at a rate of 100 mL / min. 3 To form an anaerobic environment, 1.25 g potassium persulfate was added to the intermediate solution under anaerobic environment, and the mixture was stirred at 30 rpm for 10 min. Then 0.25 g N,N'-methylenebisacrylamide was added, and the polymerization reaction was carried out at 60 ° C for 3 h. After the polymerization reaction was completed, the introduction of NH 3 The product of the polymerization reaction was dried at 60°C for 12 hours and crushed to obtain a water-absorbing gel with a particle size of 100 meshes.
[0074] 1 g of ascorbic acid was completely dissolved in 160 mL of deionized water to obtain an ascorbic acid aqueous solution, 1.2 g of water-absorbing gel was added to the ascorbic acid aqueous solution, and adsorbed for 90 minutes. The adsorbed product was placed at 60° C. and dried for 24 hours to obtain a temperature-controlled targeted release composite inhibitor.
[0075] The particle size of the temperature-controlled targeted-release composite inhibitor prepared in this example is 160 meshes.
[0076] The temperature-controlled targeted-release composite inhibitor prepared in Example 1 was tested for liquid absorption rate, repeated liquid absorption and coal spontaneous combustion inhibition effect.
[0077] The steps for the liquid absorption rate test are as follows:
[0078] The temperature-controlled targeted release composite inhibitor was placed in a tea bag, and the tea bag was immersed in deionized water, KCl aqueous solution, NaCl aqueous solution and MgCl 2 Let the water stand for 30 minutes, take out the tea bag and weigh it. Calculate the liquid absorption rate, where Q is the liquid absorption rate, g / g; m is the total mass of the tea bag after liquid absorption, g; m 1 is the initial mass of the composite inhibitor for temperature-controlled targeted release, g; m 2 The weight of the tea bag is g.
[0079] The test results show that at 25°C, the maximum water absorption rate of the temperature-controlled targeted-release composite inhibitor of Example 1 reaches 782.4 g / g.
[0080] Figure 1 The composite inhibitor for temperature-controlled targeted release of Example 1 was respectively dissolved in KCl aqueous solution, NaCl aqueous solution and MgCl aqueous solution at different mass concentrations. 2 Absorption rate in aqueous solution. Figure 1 It can be seen that the temperature-controlled targeted release composite inhibitor has a great influence on Na + The maximum liquid absorption rate of the salt solution reaches 212.8 g / g. The order of liquid absorption rate of the temperature-controlled targeted release composite inhibitor of the present invention in different cationic salt solutions is: Na + >K + >Mg 2+ .
[0081] The above-mentioned liquid absorption rate test method is used to measure the liquid absorption rate of the temperature-controlled targeted release composite inhibitor in deionized water at different temperatures.
[0082] Figure 2 The composite inhibitor for temperature-controlled targeted release of Example 1 at different temperatures was respectively dissolved in water, MgCl with a mass concentration of 0.2%, 2 Absorption rate in aqueous solution. Figure 2 It can be seen that as the temperature rises, the three-dimensional network structure of the composite inhibitor is easily destroyed, resulting in a gradual decrease in the liquid absorption rate; when the temperature exceeds 60°C, the liquid absorption rate drops sharply; when the temperature reaches 90°C, the liquid absorption rate is only 39.5% of that at 25°C.
[0083] Using the above-mentioned liquid absorption rate test method, at 25°C, when the temperature-controlled targeted release composite inhibitor reaches the maximum liquid absorption rate in deionized water, the composite inhibitor is taken out and placed at 60°C to dry for 2 hours, and then the liquid absorption rate of the composite inhibitor in deionized water is tested again at 25°C.
[0084] Figure 3 is the repetitive liquid absorption ratio of the temperature-controlled targeted release composite inhibitor in Example 1 in water. Figure 3 It can be seen that the temperature-controlled targeted release composite inhibitor of the present invention has a good repeated liquid absorption rate. The result shows that the composite inhibitor can be repeatedly recycled to achieve multiple coverage of the coal body, isolate the coal body from oxygen, and release moisture as the coal temperature rises to achieve a cooling effect.
[0085] Application Example 1
[0086] 50 g of the temperature-controlled targeted-release composite inhibitor prepared in Example 1 was mixed with 250 g of raw coal and dried in vacuum at 133 Pa and 30° C. for 24 h. After being taken out, the mixture was placed in a coal sample tank, and the change in CO content during the heating process was determined using a coal spontaneous combustion programmed temperature test device.
[0087] Application Comparative Example 1
[0088] The composite inhibitor for temperature-controlled targeted release in Experimental Example 1 was replaced with the water-absorbing gel prepared in Example 1, and the rest was the same as in Application Example 1.
[0089] Application Comparative Example 2
[0090] The temperature-controlled targeted release composite inhibitor in Application Example 1 is replaced with tea polyphenols, and the rest is the same as Application Example 1.
[0091] Application Comparative Example 3
[0092] The temperature-controlled targeted release composite inhibitor in Application Example 1 is omitted, and the rest is the same as Application Example 1.
[0093] Figure 4 The CO content changes during the raw coal oxidation process in Application Example 1 and Comparative Examples 1 to 3 are shown. Figure 5 The inhibition rates of application example 1 and comparative examples 1 to 3 during the raw coal oxidation process are shown in FIG. Figure 4 , 5 It can be seen that the temperature-controlled targeted-release composite inhibitor of the present invention can effectively inhibit the oxidation reaction of coal and inhibit the spontaneous combustion of coal.
[0094] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a temperature-controlled targeted release composite inhibitor, characterized in that: The following steps are included: (1) neutralizing an acrylic acid solution, cellulose, acrylamide and water to obtain an intermediate solution; (2) subjecting the initiator, the crosslinking agent and the intermediate solution to a polymerization reaction to obtain a water-absorbing gel; (3) The water-absorbing gel is immersed in an aqueous solution of an antioxidant for adsorption, thereby obtaining a temperature-controlled targeted release composite inhibitor.
2. The preparation method according to claim 1, characterized in that: The cellulose comprises one or more of methyl cellulose, hydroxymethyl cellulose, hydroxypropyl methyl cellulose and sodium carboxymethyl cellulose; The initiator comprises potassium persulfate, an azo compound or 2-hydroxy-2-methyl-1-phenylpropanone; The cross-linking agent was N,N'-methylenebisacrylamide; The antioxidant comprises one or more of ascorbic acid, tea polyphenols, anthocyanidins and grape seed extract.
3. The preparation method according to claim 1 or 2, characterized in that: The acrylic acid solution in step (1) is a mixture of acrylic acid and sodium hydroxide, the neutralization degree of the acrylic acid solution is 40-90%, the mass ratio of cellulose to acrylic acid is 5-30:100, the mass ratio of acrylamide to acrylic acid is 18-45:100, and the mass volume ratio of cellulose to water is 5-30g:200mL.
4. The preparation method according to claim 3, characterized in that: The temperature of the neutralization reaction in step (1) is 60 to 80° C., and the time of the neutralization reaction is 20 to 40 minutes.
5. The preparation method according to claim 4, characterized in that: The mass ratio of the initiator in step (2) to the acrylic acid in the acrylic acid solution in step (1) is 0.2 to 1:100, and the mass ratio of the crosslinking agent to the acrylic acid in the acrylic acid solution in step (1) is 0.07 to 0.2:
100.
6. The preparation method according to claim 4 or 5, characterized in that: The polymerization reaction temperature in step (2) is 60-80° C., and the polymerization reaction time is 1-3 hours; the polymerization reaction is carried out in an oxygen-free environment.
7. The preparation method according to claim 6, characterized in that: In step (3), the mass ratio of the water-absorbing gel to the antioxidant is 0.8-1.2:1, and the mass volume ratio of the antioxidant to water in the antioxidant aqueous solution is 1g:80-200mL.
8. The preparation method according to claim 7, characterized in that: The adsorption time in step (3) is 90 to 150 minutes.
9. The temperature-controlled targeted release composite inhibitor prepared by the preparation method according to any one of claims 1 to 8, characterized in that: The particle size of the temperature-controlled targeted-release composite inhibitor is 80-160 meshes.
10. The use of the temperature-controlled targeted release composite inhibitor according to claim 9 in inhibiting coal spontaneous combustion, characterized in that: The composite inhibitor with temperature-controlled targeted release and coal are mixed, and the mass ratio of the composite inhibitor with temperature-controlled targeted release and coal is 1:3-8.
Citation Information
Cited By
Preparation process of high polymer coal spontaneous combustion inhibitor
CN120248414A
Preparation process of high polymer coal spontaneous combustion inhibitor
CN120248414B
An environmentally friendly composite fire retardant and extinguishing agent, its preparation method and application
CN122702099A